Literacy rate impact on innovations and environmental pollution in China - Jiang, Na; Nuţă, Alina Cristina; Zamfir, Cristina Gabriela (Frontiers in Environmental Science, 2023)
This study examines the impact of literacy rate and innovations on environmental pollution in China from 1990 to 2021. We applied the Quantile ARDL method for the analysis, and our findings suggest that an increase in literacy rate leads to short- and long-term innovations. At the same time, literacy has a positive effect in 1st to 4th quantile in the long run. Furthermore, innovation has a positive effect on environmental pollution. However, in the short run, the literacy rate has negative implications for environmental pollution. These findings imply that education is essential to increase innovation in the economy. Besides, the literacy rate increases the standard of living, and thus, it is recommended that government should adopt environmental protection laws to reduce environmental pollution along with literacy increase. Additionally, China has achieved significant economic growth in the last few decades. To ensure sustainable economic growth government should introduce a carbon tax to minimize production externalities such as environmental pollution.